Wetland Fires and Its Environmental Conditions - Mona Lestari; Desheila Andarini; Anita Camelia; Novrikasari Novrikasari; Rizka Faliria Nandini; Poppy Fujianti (School of Postgraduate Studies, Diponegoro Univer, 2021)
Today, many wetlands have been converted into agricultural, industrial, and residential areas. This conversion of land functions creates new problems for the environment and human, one of which is land fires. The results of land fires can also cause other problems that results in losses in various fields, such as human health, the economy, and other fields. The emergence of smog as a result of land fires can cause respiratory problems, disruption of the transportation system, conflicts between neighboring countries, and the others. South Sumatra Province is one of the largest contributors to the haze as a result of land fires, especially its wetlands. Ogan Ilir Regency is one of the areas in South Sumatra Province which has extensive wetlands and fires frequently occur. Fires are caused by triggering factors, one of which is natural factors such as a prolonged dry season, availability of water supply, and intensity of rainfall. This study is an analytic descriptive study that aimed to provide an overview of environmental conditions on land, the majority of which are wetlands which experienced fires in Ogan Ilir Regency in 2019. The environmental conditions studied included soil and vegetation types. The data obtained will be displayed through tables and graphs, then interpreted and analyzed descriptively. The type of data used is secondary data in the form of a report by the Regional Disaster Management Agency Ogan Ilir Regency related to land fires in OI Regency and processed using the Geographic Information System (GIS) application. The results of the analysis show that the area of land fires that mostly occurred in North Indralaya District was 382,7 hectares with a total of 144 hotspots. The burnt area was dominated by peat soil (53%) and scrub vegetation (43%).